2011
DOI: 10.1261/rna.2500711
|View full text |Cite
|
Sign up to set email alerts
|

Active site mapping and substrate specificity of bacterial Hen1, a manganese-dependent 3′ terminal RNA ribose 2′O-methyltransferase

Abstract: The RNA methyltransferase Hen1 and the RNA end-healing/sealing enzyme Pnkp comprise an RNA repair system encoded by an operon-like cassette present in bacteria from eight different phyla. Clostridium thermocellum Hen1 (CthHen1) is a manganesedependent RNA ribose 29O-methyltransferase that marks the 39 terminal nucleoside of broken RNAs and protects repair junctions from iterative damage by transesterifying endonucleases. Here we used the crystal structure of the homologous plant Hen1 to guide a mutational anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…Although changes in the substrate preferences of nucleic acid enzymes in response to varying the divalent cation are often dismissed as in vitro quirks, our experience with enzymes that mediate bacterial NHEJ and bacterial RNA repair has taught us that the ligase, polymerase, 3′-phosphoesterase, and methyltransferase components of these repair pathways require manganese for catalysis and are either inactive or poorly active with magnesium. 26-34 Studies of the radio-resistant bacterium Deinococcus have revealed that manganese exerts profound effects on its sensitivity to radiation and oxidative stress in vivo . 35,36 The observed ablation of both the Mn 2+ and Mg 2+ dependent activities of mycobacterial PNPase by the D526A mutation argues that they bind to the same site on the enzyme, corresponding to the site defined by the crystal structure of an E. coli PNPase·Mn 2+ complex.…”
Section: Discussionmentioning
confidence: 99%
“…Although changes in the substrate preferences of nucleic acid enzymes in response to varying the divalent cation are often dismissed as in vitro quirks, our experience with enzymes that mediate bacterial NHEJ and bacterial RNA repair has taught us that the ligase, polymerase, 3′-phosphoesterase, and methyltransferase components of these repair pathways require manganese for catalysis and are either inactive or poorly active with magnesium. 26-34 Studies of the radio-resistant bacterium Deinococcus have revealed that manganese exerts profound effects on its sensitivity to radiation and oxidative stress in vivo . 35,36 The observed ablation of both the Mn 2+ and Mg 2+ dependent activities of mycobacterial PNPase by the D526A mutation argues that they bind to the same site on the enzyme, corresponding to the site defined by the crystal structure of an E. coli PNPase·Mn 2+ complex.…”
Section: Discussionmentioning
confidence: 99%
“…In methyl transferases with tRNA as the acceptor, while metal ions are required for activity (Hurwitz, et al, 1964), this requirement is believed to stabilize the tertiary structure of the nucleic acid (Gong, et al, 2002). Recently, a metal-dependent O-methyl transferase involved in tRNA repair was identified (Jain and Shuman, 2011), although the precise role of the metal ion is unknown. Thus, most of the AdoMet-dependent methyl transferases require no metal ions for methyl transfer; for those that do, metal ions are used to modulate substrate binding and selectivity but not catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,10,11 The C-terminal half of Hen1 is an autonomous Mn 2+ -dependent 3′-terminal ribose 2′-O-methyltransferase that places a 2′-OCH 3 mark at the RNA repair junction prior to ligation and thereby protects the junction from recurrent damage. 4,5,12,13 …”
mentioning
confidence: 99%